Cleavage and development in cultured preimplantation mouse embryos exposed to lidocaine - Del Valle L.J. (1996)
Acknowledgments -This investigationw as supportedb y a grant from the Sciences and Technology National Council (CONCYTEC, Project No 2043) Lima-Peru.